1987
DOI: 10.1136/gut.28.suppl.193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pancreatic atrophy and hypertrophy on the small intestine.

Abstract: SUMMARY Intestinal enzyme activities were investigated in mice with spontaneously occurring exocrine pancreatic insufficiency (EPI), in rats after induction of pancreatic insufficiency by intraductal injection of oleic acid, and in rats after feeding a proteinase inhibitor (Camostate) which induced a marked pancreatic hypertrophy. An increase in saccharase activity and in vitro uptake of L-phenylalanine was found in EPI mice, while activities of alkaline phosphatase and lactase were not altered. In oleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In rats, after surgical transposition of intestinal segments, it has been shown that intestinal growth and villi morphology was dependent on the direct contact with the pancreatic juice [11,12]. Furthermore, in hamsters with experimentally induced EPI by pancreatic duct ligation or in mice that spontaneously develop EPI, it has been demonstrated that the lack of pancreatic juice affected the intestinal morphology causing villi atrophy and an increased expression of brush-border enzymes [13][14][15]. However, in another rat study no morphological differences in the small intestine were observed between pancreatic duct-occluded animals and controls [16].…”
Section: Introductionmentioning
confidence: 98%
“…In rats, after surgical transposition of intestinal segments, it has been shown that intestinal growth and villi morphology was dependent on the direct contact with the pancreatic juice [11,12]. Furthermore, in hamsters with experimentally induced EPI by pancreatic duct ligation or in mice that spontaneously develop EPI, it has been demonstrated that the lack of pancreatic juice affected the intestinal morphology causing villi atrophy and an increased expression of brush-border enzymes [13][14][15]. However, in another rat study no morphological differences in the small intestine were observed between pancreatic duct-occluded animals and controls [16].…”
Section: Introductionmentioning
confidence: 98%
“…This intestinal growth was probably secondary to an increased luminal load, due in turn to maldigestion and malabsorption resulting from inhibition of proteolytic enzymes. Food residues may stimulate gut growth (Johnson, 1987), and intestinal growth and functional small intestinal hypertrophy have been shown in mice with spontaneous exocrine pancreatic insufficiency (although morphological evidence of hypertrophy was not found; Adler et al 1987).…”
Section: Discussionmentioning
confidence: 99%